2020
DOI: 10.1080/00325481.2020.1841988
|View full text |Cite
|
Sign up to set email alerts
|

Pain severity and healthcare resource utilization in patients with osteoarthritis in the United States

Abstract: Objective: To evaluate healthcare resource utilization (HCRU) by osteoarthritis (OA) pain severity. Methods: Cross-sectional surveys of US physicians and their patients were conducted between February and May 2017. Using the Numeric Rating Scale, patients were classified by self-reported pain intensity in the last week into mild (0-3), moderate (4-6), and severe (7-10) cohorts. Parameters assessed included clinical characteristics, HCRU, and current caregiver support. Descriptive statistics were obtained, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
(42 reference statements)
5
22
0
Order By: Relevance
“…While moderate-to-severe OA pain respondents were significantly more likely to be female and of working age (<65 years), they were also less likely to be employed and have an income ≥$75,000. These trends in employment and income were reported in both Zhao et al 19 and Nalamachu et al 25 Similarly, the significantly greater prevalence of clinical comorbidities in moderate-to-severe respondents is consistent with those two studies; however, depression and insomnia were 2- to 4-fold greater, respectively, in the mild OA pain cohort in our study. Although these differences likely reflect the mild cohort definition, they may also be due to use of self-report in the current study relative to diagnostic coding in administrative claims or a physician-reported diagnosis in the medical chart at the time of the visit for OA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While moderate-to-severe OA pain respondents were significantly more likely to be female and of working age (<65 years), they were also less likely to be employed and have an income ≥$75,000. These trends in employment and income were reported in both Zhao et al 19 and Nalamachu et al 25 Similarly, the significantly greater prevalence of clinical comorbidities in moderate-to-severe respondents is consistent with those two studies; however, depression and insomnia were 2- to 4-fold greater, respectively, in the mild OA pain cohort in our study. Although these differences likely reflect the mild cohort definition, they may also be due to use of self-report in the current study relative to diagnostic coding in administrative claims or a physician-reported diagnosis in the medical chart at the time of the visit for OA.…”
Section: Discussionsupporting
confidence: 92%
“…Significantly greater HCRU across all categories in the prior 6 months was observed in moderate-to-severe OA respondents compared with mild OA. While similar trends in resource utilization were generally observed in the other studies, 19 , 22 , 25 heterogeneity in measurement and definitions precludes meaningful comparisons.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Several factors are associated with high levels of healthcare utilization due to pain. 7,15 These include older age, 7,15,16 low socioeconomic status, 7,16 marital status (people never married seek healthcare less often than those married) 17 and being female, 7,15,18 high pain intensity, [18][19][20] high level of disability, 18,19,21 number of pain sites, 21 comorbidity, 16 body mass index (BMI), poor general health, 15,16,22 negative health beliefs (health anxiety, catastrophizing, fear avoidance), 15,22,23 being retired or unemployed, 8 and previous healthcare use. 22,24 Personality has also been suggested as an important factor in the development of pain and coping strategies -including healthcare-seeking.…”
Section: Video Abstractmentioning
confidence: 99%
“…Throughout the literature, the DSP methodology has been used to assess the relationships between diseases and/or symptoms of disease with HCRU [33][34][35] ; nonetheless, there are some limitations to this specific study that should be highlighted. As PRFs were completed by neurologists for the next 10 to 12 consecutively consulting patients with PD, the sample collected was pseudo-random, rather than a truly random sample.…”
Section: Discussionmentioning
confidence: 99%